2019
DOI: 10.1111/gcb.14726
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate addition stimulates microbial decomposition of organic matter in salt marsh sediments

Abstract: Salt marshes sequester carbon at rates more than an order of magnitude greater than their terrestrial counterparts, helping to mitigate climate change. As nitrogen loading to coastal waters continues, primarily in the form of nitrate, it is unclear what effect it will have on carbon storage capacity of these highly productive systems. This uncertainty is largely driven by the dual role nitrate can play in biological processes, where it can serve as a nutrient-stimulating primary production or a thermodynamical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 115 publications
4
39
1
Order By: Relevance
“…5 and 7). In a different study that sequenced the 16S rRNA genes from this experiment, several taxa belonging to groups known to reduce SO 4 − increased in abundance in the unamended treatment (i.e., Desulfobacterales and Desulfarculales; Bahr et al 2005;Bulseco et al 2019). Furthermore, several L4 functions related to nitrogen fixation (NifN, NifE, NifU, and NifA;Gussin et al 1986;Kuypers et al 2018) were positively correlated with SO 4 2− reduction and negatively correlated with NO 3 − reduction-related pathways, suggesting that the promotion of SO 4 − reducers (and, in contrast, their inhibition by excess supply of NO 3 − in the enhanced treatment) is important in enhancing the functional potential for nitrogen fixation.…”
Section: Resource Limitation In the Unamended Treatmentmentioning
confidence: 87%
“…5 and 7). In a different study that sequenced the 16S rRNA genes from this experiment, several taxa belonging to groups known to reduce SO 4 − increased in abundance in the unamended treatment (i.e., Desulfobacterales and Desulfarculales; Bahr et al 2005;Bulseco et al 2019). Furthermore, several L4 functions related to nitrogen fixation (NifN, NifE, NifU, and NifA;Gussin et al 1986;Kuypers et al 2018) were positively correlated with SO 4 2− reduction and negatively correlated with NO 3 − reduction-related pathways, suggesting that the promotion of SO 4 − reducers (and, in contrast, their inhibition by excess supply of NO 3 − in the enhanced treatment) is important in enhancing the functional potential for nitrogen fixation.…”
Section: Resource Limitation In the Unamended Treatmentmentioning
confidence: 87%
“…Marsh shoreline erosion was 2.5 times higher after oiling and the marsh will not recover (Turner et al, 2016). Diversions of the Mississippi water to deltaic wetlands for restoration (a point-source) or cultural eutrophication (non-point source) increase the availability of nitrogen and phosphorous to the wetlands, contributing to general eutrophication of the delta, which also affects the state of the soils and causes carbon losses (Darby and Turner, 2008;Kearney et al, 2011;Deegan et al, 2012;Bulseco et al, 2019).…”
Section: Mississippi River Delta Coastal Wetlands United Statesmentioning
confidence: 99%
“…Studies of bacterial community structures and nitrogen cycling in several coastal lagoons found that physical gradients and nutrients affect sediment microbial interactions and function [19,24]. In marine sediments exposed to high nutrients, studies reported dramatic changes in ecological function, but no significant differences in microbial community structure [25][26][27].…”
Section: Introductionmentioning
confidence: 99%